Design and development of a portable electronic nose and its application for lard detection in food - Nurul Asyikeen binti Ab. Mutalib (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
This study has been successfully conducted to develop a method for rapid detection of lard adulteration in food using portable electronic nose (E-Nose). E-Noses used in the food industry are big and not portable, so the portable E-Nose prototype was designed as a small, user-friendly device with several functions such as having a keypad, LCD screen, small chamber, hot plate, USB port and two fans mounted on the chamber to aid the detection process. This thesis outlines an experimental study to optimize on how low the weight of lard can be detected by the portable E-Nose. The use of raw lard as a means of calibration was conducted with minimum lard's weight detected was 0.2g. The hypothesis was also successfully proven which the highest sensor response was determined at the highest temperature of air inside the E-Nose chamber with 518, 525 and 532 for 0.2g, 0.4g and 0.6g of lard, respectively. While for the statistical analysis, it was generated using Design Expert 7.1.5 which the quadratic model generated was significant based on the Analysis of Variance (ANOVA). For optimization process, optimum time and temperature obtained from Response Surface Methodology (RSM) was 3.0 minutes of the detection when the temperature of air inside the chamber is 50°C. While for validation process, pie samples with no lard added, has recorded the highest sensor response of 472 which is occurring because of the increasing humidity surrounded the gas sensor. However, when adding 2% (g/g) of lard into the pie, it has increased the response to 474, 501 and 500 for 50°C, 100°C and 150°C. This study had also determined that it can screen the presence of lard adulteration in chocolate, biscuit, cake and bread that are sold in the market. Both chocolate B and biscuit C shows the baseline of sensor response of 470 since it has halal logo from JAKIM and from the halal authority of the neighbouring country. Hence, the portable E-Nose developed for this study is found to be a reliable handheld detector which can be used for travelling and quick detection of foods.